Political economies of education and violent public protests in conflict zone: narratives of youth from iNanda and KwaMashu townships, South Africa - Spambo, Nyameka (Frontiers in Education, 2025)
Protests accompanied by increasing violence are prevalent in the townships of South Africa. These violent protests often arise from community dissatisfaction with service delivery, which in some cases leaves residents without basic necessities such as water and electricity. As a result, learners and students are left without access to schools, colleges, and universities, disrupting education programs. This study draws on Novelli and Cardozo-Lopez’s framework, which identifies a tool that can aid in alleviating poverty. This study also considers both physical and structural forms of violence and examines how the everyday experiences of youth are shaped by these dynamics. In conflict zones such as the iNanda and KwaMashu townships, education suffers whenever violent events take place. This study is framed by Political Economy Analysis (PEA), which was used to explore how the intersections of politics, geographic location, history, and class shape experiences of both formal and informal education. This qualitative study used semi-structured interviews with 16 participants and two focus groups involving youth and learners aged 19 to 35 years. Findings from the thematic analysis, as guided by the 4R’s framework (recognition, redistribution, representation and reconciliation), indicate that (1) violent protests are directly linked to dissatisfaction with service delivery, which negatively influences the education system, and (2) youth in conflict zones are deprived of formal education, often becoming exposed to adults who teach or engage them in criminal activities; and (3) communities in the iNanda and KwaMashu townships deem community dialogue and the Ubuntu approach as possible solutions to protect youth from the consequences of various forms of violence. The study concludes that since no community in the world is immune to physical or structural violence, education can serve as a powerful vehicle for promoting social justice among youth in conflict zones.